Extrato formulado de Rosmarinus officinalis, Curcuma longa e Pycnoporus sanguineus para controle de Alternaria solani e de Xanthomonas vesicatoria em tomateiro: tempo de prateleira, concentração e intervalo de aplicação - Assi, Lindomar (2012)
Due the environmental pollution and damages in non-target organisms, by the indiscriminate use of pesticides in agriculture, it is necessary the search for new plant diseases control technology. The objective of this study was to evaluate the in vitro antimicrobial activity against Alternaria solani and Xanthomonas vesicatoria and the control of early blight and bacterial spot on tomato plants, using stable formulation, as soluble powder, from Rosmarinus officinalis, Curcuma longa and Pycnoporus sanguineus fruiting body. To determine the shelf life, the soluble powder was kept at 40 oC during 0, 60, 120 and 180 days and assayed with five concentrations (0, 50, 100, 150 and 200 mg L-1). When the shelf life and the best concentrations were defined, it was evaluated the timeinterval of spraying of seven, 14 and 21 days. As control treatments were used the fungicides azoxystrobin (200 mg of active ingredient a.i L-1) to early blight and oxychloride (400 mg a.i. L-1) to bacterial spot. There were no in vitro antifungal and antibacterial activities from all extracts. The calculated concentration of P. sanguineus extract for the best control of diseases was 130 mg L-1, with 24 months of shelf live to soluble powder. In vivo, the three extracts, spraying weekly gave the same control of fungicides to early blight and bacterial spot, with values of disease reduction up to 75% for rosemary and turmeric and 79% for P. sanguineus. These results show that the aqueous extract obtained from R. officinalis, C. longa and P. sanguineus soluble powder formulation, can protect tomato plants against early blight and bacterial spot, probably by resistance induction